Paul Ricœur et la narratologie : un dialogue croisé - Ioana Vultur (Cahiers de Narratologie)
The article focuses on the cross-dialogue between Ricœur and narratology. On the one hand, Ricoeur entered into a debate with structuralist narratology, not only in order to oppose the openess of discourse to the closure of the text, but also in order to integrate narratology into his own model. He developed his hermeneutical model taking narratology as a departure point (Genette), by introducing the central notion of « world of the text » to which corresponds, according to him, a « fictive experience of the reader ». On the other hand, Ricœur’s model had an impact on poststructuralist narratology, particularly on cognitive narratology, which developed possibilities contained in nuce in Time and narrative and also tried to connect the analysis of textual structures with the experience of the reader. The central notion of « experientiality » introduced by Monika Fludernik, replaces the debate of the articulation between plot and experience in the context of narratology.